Carbon Dots as a Potential Therapeutic Agent for the Treatment of Cancer‐Related Anemia. Issue 19 (9th April 2022) - Xu, Yuanlin; Wang, Boyang; Zhang, Mingming; Zhang, Jingxin; Li, Yudong; Jia, Peijun; Zhang, Huan; Duan, Lulu; Li, Yan; Li, Yating; Qu, Xiaoli; Wang, Shihui; et al.
Abstract: Due to the adverse effects of erythropoietin (EPO) on cancer patient survival, it is necessary to develop new agents that can be used to efficiently manage and treat cancer‐related anemia. In this study, novel distinctive carbon dots, J‐CDs, derived from jujube are designed, synthesized, and characterized. Based on the obtained results, this material comprises sp 2 and sp 3 carbon atoms, as well as oxygen/nitrogen‐based groups, and it specifically promotes the proliferation of erythroid cells by stimulating the self‐renewal of erythroid progenitor cells in vitro and in vivo. Moreover, J‐CDs have no discernible effects on tumor proliferation and metastasis, unlike EPO. Transcriptome profiling suggests that J‐CDs upregulate the molecules involved in hypoxia response, and they also significantly increase the phosphorylation levels of STAT5, the major transducer of signals for erythroid progenitor cell proliferation. Overall, this study demonstrates that J‐CDs effectively promote erythrocyte production without affecting tumor proliferation and metastasis; thus, they may be promising agents for the treatment of cancer‐related anemia. Abstract : Owing to the adverse effects of erythropoietin (EPO) on cancer patient survival, it is necessary to develop new agents for cancer‐related anemia treatment. Therefore, novel carbon dots, J‐CDs, derived from jujube are designed. J‐CDs specifically promote the proliferation of erythroid cells by stimulating the self‐renewal of erythroid progenitor cells. Moreover, J‐CDs have no discernible effects on tumor proliferation, unlike EPO.